侵襲性真菌症の原因菌に対して抗真菌作用を有する新規化合物の探索と合成 - 中田（本川）, 奈々 (Wiley-VCH, 2020)
Nagasaki University (長崎大学) 博士(医学) Invasive fungal infections are growing causes of morbidity and mortality in immunocompromised patients. However, only one antifungal drug class has been developed in the last 30?years, extremely limiting current therapeutic options. To address unmet medical needs, we performed high-throughput screening of 9600 chemical compounds and identified an aminohydrazone derivative as a novel and potent antifungal compound. We then designed and synthesized a series of aminohydrazone derivatives, and demonstrated that 1-[(E)-[4-(3′,4′-dichlorobenxyloxy)phenyl methylidene]amino]-guanidine had the most potent inhibitory activity and exhibited a broad spectrum of antifungal activities against Candida species (including multidrug resistant C. auris), Aspergillus species, Cryptococcus neoformans, and Rhizopus oryzae. Against C. albicans, the leading cause of Candida infections, the compound had fungicidal activity for planktonic cells at 8?μg mL?1 (25?μM) and anti-biofilm activity at 34?μg mL?1 (100?μM). This study provides new insights for the development of a new drug class for the treatment of invasive fungal infections which are often refractory to conventional therapies. 長崎大学学位論文 学位記番号:博(医歯薬)甲第1223号 学位授与年月日:令和2年3月19日 Author: Nana Nakada-Motokawa, Taiga Miyazaki, Satoshi Mizuta, Yoshimasa Tanaka, Tatsuro Hirayama, Takahiro Takazono, Tomomi Saijo, Kazuko Yamamoto, Yoshifumi Imamura, Koichi Izumikawa, Katsunori Yanagihara, Koichi Makimura, Kohsuke Takeda, Shigeru Kohno, Hiroshi Mukae Citation: ChemistrySelect, 5(3), pp.1140-1145; 2020 Nagasaki University (長崎大学), 博士(医学) (2020-03-19) doctoral thesis